Pengaruh Model Pembelajaran Kreatif Terhadap Kemampuan Lateral Thinking pada Materi Aritmatika Sosial di MI Miftahul Ulum Tempurejo Jember - Crismono, Prima Cristi; Sunardi, Sunardi; Susanto, Susanto; Suwito, Abi (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2024)
This study aims to examine the influence of creative learning models on students' lateral thinking skills in social arithmetic material. The problem addressed is the low creative thinking ability of students who only use traditional problem-solving methods. The method used is quasi-experimental with a posttest-only control design, involving two groups of fifth-grade students at MI Miftahul Ulum Tempurejo Jember. Data were collected through formative tests measuring lateral thinking skills. The analysis results show that the creative learning model significantly influences the improvement of students' lateral thinking skills. In conclusion, the creative learning model is effective in enhancing lateral thinking skills and is recommended for use in mathematics teaching to develop students' creative thinking abilities.